INTERNAL EDUCATIONAL QUALITY ASSESSMENT ANALYSIS, MAHACHULALONGKORNRAJAVIDYALAYA UNIVERSITY KHON KAEN CAMPUS, ACADEMIC YEAR 2014 - 2019 - Saengduenchay, Ruedee (Journal of Graduate MCU KhonKaen Campus, 2020)
This research aims to analyze and find guidelines for quality improvement from the results of internal educational quality assessment at the curriculum level academic year 2014 - 2019, Mahachulalongkornrajavidyalaya University, Khon Kaen Campus. The results of the internal educational quality assessment of Mahachulalongkornrajavidyalaya University, Khon Kaen Campus, academic year 2014 - 2019 were found as follows: Results of internal education quality assessment Curriculum level 6 components 13 indicators as follows (1.1) Academic year 2014, there were 10 assessed courses, the average score from all courses was 0.52, low-level operations, the score was between 1.37 - 1.99 points. (1.2) Academic year 2015, there were 12 courses audited, overall the average score from all courses was 2.96, fair level operation, the score was between 2.22 - 3.52 points. (1.3) Academic year 2016, 12 courses were audited, overall the average score of all courses is 2.82, fair level operation, score is between 2.06 - 3.32 points. (1.4) Academic year 2017, there are 13 courses audited, overall the average score of all courses is 3.40, good performance, score is between 2.12 - 3.84 points. (1.5) Academic year 2018, there were 14 courses audited, overall the average score of all courses was 3.78, good performance score between 2.15 - 4.10 points (1.6) Academic year 2019, there are 12 courses audited, overall the average score from all courses is 2.92, fair level operation, the score is between 2.27 - 3.50 points, while the score from the internal quality assessment results. At Khon Kaen campus level, 5 elements, 13 indicators, during the academic year 2014 - 2019, in overall, was at a good level (x ̅ = 4.25). When considering all 5 aspects, the efficiency and effectiveness of quality assurance were at a very good level in 3 aspects. The following are ordered in order: 1. Art and culture conservation (x ̅ = 4.83) 2. Management (x ̅ = 4.75) 3. Academic service (x ̅ = 4.67) Research and graduate production. Found that the efficiency and effectiveness of quality assurance Good level in research (x ̅ = 4.50) in graduate production (x ̅ = 3.74) Guidelines for quality development from the results of educational quality assessment within the academic year 2014 - 2019, Khon Kaen Campus The strategy map should be reviewed following the strategic plan and the strategic plan as a single mechanism. For all courses to develop another quality system that is challenging and able to reflect the quality of performance and drive the development of teaching and learning agencies and universities to develop to excellence (Edpex), which should build a team. That can develop research and quality assurance that can be integrated and facilitate various quality systems to increase incentives to cover every mission for people at all levels of work It may take some time to operate. Continuous improvement and development.